EVALUASI PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA ( DESA REJO MULYO KECAMATAN WAY SERDANG KABUPATEN MESUJI TAHUN 2014) - Isabella Isabella; Julio Sesar; Amaliatulwalidain Amaliatulwalidain (Jurnal Pemerintahan dan Politik, 2019)
House Renovation program is building house or housing built on the invitiative, and afforts of the include repair, restoration/ expansion or construction of new homes and their environment. House Surgery Program aims to assist Low-Income Communities in building livable housing for public welfare. The purpose of this study is to describe about the process and its implementation and problematic that happened in the vilage Rejo Mulyo Sub Districh Way Serdang Mesuji Districh year 2014. Based on the research results ; (1) Implementation of the house surgeon , at the first stage raises the problem that occurs miss communication between the community and the government resulting in one of the public perception of to the terms specified by BAPPEDA for the disbursement of the second stage , so that people are forced to seek a loan to continue construction of the half- finished to complete the requirements not supposed. (2) there are some rules that the setregional regulatory agenciesodd lies in the requirement to have this assistance housing stimulant assistance, recipient family must have a self-financing in the form of savings that you can use additional funds housing stimulant assistance, This shows that the program is not entirely aimed at the poor , but d aimed at the middle to lower. (3) After the implementation of this progra can say karnakan successfully been applied in various villages in Mesuji and received appreciation from the local community .Keyword : Policy Evaluation & Problemika in Program Implemention